Anniversaries in history of morphology in 2016 - S. A. Kutya (Морфологія, 2016)
500 years ago was born Realdo Colombo (Matteo Realdo Colombo, latinized by Renaldus Columbus, 1516 or 1515-1559) - an Italian surgeon and anatomist. He studied surgery under the guidance of the famous Venetian surgeon Giovanni Antonio Lonjo, then entered the University of Padua, where he was a student of A.Vesalia.